Tibia and femur biometrics of japanese quails fed increasing levels of extruded soybeans (Research, Society and Development, 2020)
The aim of this study was to evaluate the effect of increasing levels of extruded soybean (0, 7.5, 15, 22.5 and 30%) in soybean meal replacement on the diet of Japanese laying quails on biometry of the tibia and femur bones. A total of 180 female quails of the species Coturnix coturnix japonica with approximately 150 days of life standardized by body weight, distributed in galvanized wire measuring 38 cm long × 40 cm wide × 23 cm height were used. The design was completely randomized (CAD), with five treatments and six replicates containing six birds per replicate. The experiment lasted for 84 days, with three cycles of production, with 28 days each cycle. There was no significant effect (p>0.05) of the inclusion of increasing levels of extruded soybean on the biometrics of the tibial and femur bones, nor was there any adverse effect on the Seedor index of these bones, which shows that they remained the same. with good resistance during all production cycles of these birds. It can be concluded that the use of extruded soybean up to 30% does not negatively influence the tibial or femur biometry of Japanese quails or the Seedor index of these bones, which shows that bone strength was not affected by inclusion of this food.